Profil Profil kesiapan berwirausaha masyarakat Dusun Tamban: Kajian fenomenologis - Suud, Fathur; IGAA Noviekayati; Amanda Pasca Rini (INNER: Journal of Psychological Research, 2023)
Abstract Based on the background of the problem regarding how the entrepreneurial readiness profile of the Tamban village community, the researcher chose a qualitative research method with a descriptive phenomenological approach. This approach was chosen because it can help researchers to obtain data that is in accordance with a qualitative approach, namely interviews by describing the findings of researchers in the field supported by descriptive phenomenology. Based on the results of the discussion above, it can be said that the community has readiness in their efforts to find out the potential for business opportunities, then develop their business, but it needs improvement in mental preparation when facing future competitors, as well as improvements regarding business capital management strategies, so that entrepreneurs in Tamban village are increasingly progress, to encourage a more prosperous life and more varied job opportunities. Based on the findings of the synthesis theme through descriptive phenomenological analysis (DPA), three essential themes were found from three participants who had unique and authentic forms of business in Tamban village, namely building shops, services ship engine service and fish smoking, three essential synthetic themes in the Tamban village community as entrepreneurs namely, confidence in facing competitors, business capital and business relations, and on the discussion of entrepreneurship readiness the community is said to be ready but needs mental improvement to face competitors and increase in the capital sector. Abstrak Berdasarkan pada latar belakang masalah mengenai bagaimana profil kesiapan Berwirausaha masyarakat Dusun Tamban, peneliti memilih metode penelitian kualitatif dengan pendekatan fenomenologis deskriptif. Pendekatan ini dipilih karena dapat membantu peneliti untuk mendapatkan data yang sesuai dengan pendekatan kualitatif yakni wawancara dengan mendeskripsikan hasil temuan peneliti di lapangan didukung dengan fenomenologi deskriptif. Berdasarkan hasil pembahasan diatas bisa dikatan masyarakat memiliki kesiapan dalam upayanya mengetahui potensi untuk dijadikan peluang usaha, kemudian mengembangkan usahanya, akan tetapi butuh peningkatan di persiapan mental ketika menghadapi kompetitor yang akan datang, serta peningkatan mengenai strategi pengelolan modal usaha, sehingga wirausaha di dusun tamban semakin maju, untuk mendorong kehidupan yang lebih makmur serta lapanagan pekerjaan yang lebih variatifBerdasarkan temuan tema sisntesis lewat analisis diskriptif phenomenological analysis (DPA), ditemukan tiga tema esensi dari tiga partisipan yang memiliki bentuk usaha yang unik dan otentik di dusun tamban, yaitu toko bangunan, jasa servis mesin kapal dan pengsapan ikan, tiga tema sistesis yang esensial di masyarakat dusun tamban sebagai pelaku wirausha yaitu, keyakinan menghadapi kompetitor, modal usaha dan relasi bisnis, dan pada pemabahasan kesiapan berwirausha masyarakat dikatakan siap akan tetapi perlu peningkatan mental untuk menghadapi kompetitor serta peningkatan di sektor modal.